Preferences for different substrates in Phalangium opilio (Opiliones: Phalangiidae) in natural environment - Novak, Tone (Acta biologica slovenica, 2009)
Phalangium opilio is the mostwidespread and one ofthe most common harvestman species in anthropogenic environments. A preliminary field experiment was carried out in Slovenia testing its preferences for different substrates. A two metres high rectangular tower with walls constituted of vertical bands of concrete, twice fired tile, wood and styrofoam was placed in a meadow. The wood proved to be the most suitable substrate, providing the most stable temperatures and moisture levels in comparison with the other experimental materials. In anthropogenic environment, various available substrates in microhabitats of Ph. opilio considerably contribute to a fine regulation of searching relatively thermally and moist-stable resting sites.
Keywords: Arachnida; Domovanje živali; Ecosystem; Ekosistem; Housing, Animal; pajkovci; sinantropija; suhe južine; zoologija